Secreted Variant of Nucleoside Diphosphate Kinase from the Intracellular Parasitic Nematode Trichinella spiralis - Gounaris, Kleoniki (American Society for Microbiology, 2001)
The molecular components involved in the survival of the parasitic nematode Trichinella spiralis in an intracellular environment are poorly characterized. Here we demonstrate that infective larvae secrete a nucleoside diphosphate kinase when maintained in vitro. The secreted enzyme forms a phosphohistidine intermediate and shows broad specificity in that it readily accepts γ-phosphate from both ATP and GTP and donates it to all nucleoside and deoxynucleoside diphosphate acceptors tested. The enzyme was partially purified from culture medium by ATP affinity chromatography and identified as a 17-kDa protein by autophosphorylation and reactivity with an antibody to a plant-derived homologue. Secreted nucleoside diphosphate kinases have previously been identified only in prokaryotic organisms, all of them bacterial pathogens. The identification of a secreted variant of this enzyme from a multicellular eukaryote is very unusual and is suggestive of a role in modulating host cell function.